The Art Form of Wedha’s Pop Art Portrait (WPAP) - Angga Kusuma Dawami; Martinus Dwi Marianto; Suwarno Wisetrotomo (Graduate School of Institut Seni Indonesia Yogyakarta, 2021)
Wedha's Pop Art Portrait (WPAP) has become one of the most popular visual arts in Indonesia since Wedha Abdul Rasyid decided on this style in 2010. A decade later, WPAP became part of visual arts in Indonesia, used by many millennial designers, sheltered by the chapter community in regions; Jakarta chapter, Jogjakarta chapter, Surabaya chapter, etc. Visual arts-based on faces is a strong characteristic of WPAP. Only a few have achieved the WPAP form in accordance with the art form that Wedha first brought up. Economic motives became the biggest influence on the change in orientation from WPAP art to commodity. Therefore, the art form in WPAP tends to follow market trends. This paper tries to define the existing art in WPAP, with the formulation of the problem: what is the art form in WPAP in Indonesia? The formal approach to art is an important part of knowing art in WPAP. Through descriptive-analytic, an explanation of the art form in WPAP according to the Wedha’s experience is presented in this paper. The analysis is using an analysis of interactions between members of the WPAP community in several chapters which already have a